Determinants of dairy cooperative membership among smallholder farmers in North-Western Ethiopia - Abateneh Molla; Azanaw Abebe; Desyalew Assefa (Cogent Food & Agriculture)
Dairy cooperative societies have a viable contribution to the reduction of poverty and improve incomes of the smallholder farmers in developing countries. Farmers in these countries are encouraged to join cooperatives to work cooperatively. However, in Ethiopia in general and in the study area in particular smallholder farmers’ cooperative membership is very low, and farmers are still hesitating to be members of dairy cooperatives. Thus, this study was planned to investigate the determinants of dairy cooperative membership among smallholder farmers. Sample diary cooperatives were selected through a simple random sampling method. For this study, cross-sectional data were collected from 266 dairy farmers through interview schedules. Determinates of dairy cooperative membership were analyzed using the binary probit model. The model result shows that dairy farming experience, family size, livestock holding, participation in training, access to market information, number of crossbreed cow ownership, and neighbors’ membership are found positively and significantly associated with dairy cooperative membership decisions. Conversely, landholding size and distance from residence to the dairy cooperative are negatively and significantly associated with dairy cooperative membership decisions. This indicates that farmers having large landholdings and far away from the dairy cooperatives are less benefited from the dairy cooperative society. The study identified that enhancing asset ownership, providing sufficient and frequent market information, providing training about dairy production, and establishing milk collection centers can improve dairy cooperative membership of farmers.